2014
DOI: 10.4103/2231-0762.127210
|View full text |Cite
|
Sign up to set email alerts
|

A survey of dental students on global oral health issues in Nigeria

Abstract: Objectives:This study seeks to investigate to what extent are students conversant with global oral health initiatives and policies, students’ willingness to volunteer service at international setting or developing countries and the need for global oral health course in Nigeria.Methods:Final year dental students in two Nigerian Universities were surveyed for this study. The students voluntarily completed the global oral health information questionnaire in a classroom before a scheduled lecture. The collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Knowledge levels did not impact the respondents’ interest and perspectives towards global health as a discipline. This pattern is consistent with other studies in LMICs, namely in India [ 17 ] and Nigeria [ 18 ], where the low levels of knowledge did not impact students’ willingness to volunteer their experiences in international settings. This contrasts with the literature in HICs [ 8 11 ] whereby first-hand exposure seems to be a determining factor in affecting students’ interests.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Knowledge levels did not impact the respondents’ interest and perspectives towards global health as a discipline. This pattern is consistent with other studies in LMICs, namely in India [ 17 ] and Nigeria [ 18 ], where the low levels of knowledge did not impact students’ willingness to volunteer their experiences in international settings. This contrasts with the literature in HICs [ 8 11 ] whereby first-hand exposure seems to be a determining factor in affecting students’ interests.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Singh & Purohit [ 17 ] and Braimoh & Odai [ 18 ] showed that many students in India and Nigeria lacked knowledge of global health. For example, in Omigoberi and Emoka’s study, few students knew about FDI and the World Health Organization’s (WHO) global oral health policy and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Braimoh et al in Nigeria [ 24 ] investigated the preparation of students to understand the status of oral health conditions globally. Half of the surveyed students stated that their dental education has “moderately” prepared, especially in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…All the surveys were anonymous, voluntary, and were carried out to all the students of the faculty (between the first and fifth grade courses) during the month of September 2022. The survey used in this study is original, however the questions about world oral health took as reference the studies of Singh and Purohit et al [23] and Braimoh and Odai et al [24] The survey was divided into 3 parts:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 7 authors were considered highly-published in this area with more than 1 publication in the final analysis (30, 31, 33-35, 38, 39, 44-52). Only 4/47 (8.5%) of articles originated from middle-income countries (36,47,69,70). There were no scholarly articles originating from low-income countries.…”
Section: Origin Of Articlesmentioning
confidence: 99%